Humanizing STEM education: an ecological systems framework for educating the whole student - Yao, Christina; Follmer Greenhoot, Andrea; Mack, Kelly; Myrick, Chandra; Poolaw, Johnny; Powell, Linda; Yarger, Lynette (Frontiers in Education, 2023)
STEM higher education in the U.S. has long been an uninviting space for minoritized individuals, particularly women, persons of color, and international students and scholars. In recent years, the contemporary realities of a global pandemic, sociopolitical divides, and heightened racial tensions, along with elevated levels of mental illness and emotional distress among college students, have intensified the need for an undergraduate STEM education culture and climate that recognizes and values the humanity of our students. The purpose of this article is to advance a more humanized undergraduate STEM education and to provide a framework to guide efforts toward achieving that vision. We argue that humanizing approaches recognize and value the complexity of individuals and the cultural capital that they bring to their education, and that this is particularly important for empowering minoritized students who are subordinated in status in STEM higher education. A STEM education that centers students' humanity gives rise to equity and promotes human well-being and flourishing alongside knowledge acquisition and skill development. We then offer a guiding framework for conceptualizing the broader ecosystem in which undergraduate STEM students are embedded, and use it to outline the individual and collective roles that different stakeholders in the ecosystem can play in humanizing STEM education.